1 If f(x) = 3x + 2 and g(x)=x+1, which expression is equivalent to (fog)(x)?

Question

1
If f(x) = 3x + 2 and g(x)=x+1, which expression is equivalent to (fog)(x)?

in progress 0
Hưng Khoa 2 weeks 2021-08-28T17:52:50+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-28T17:54:35+00:00

    Answer:

    3(x+1) + 2

    Step-by-step explanation:

    0
    2021-08-28T17:54:47+00:00

    Answer:


    (3x+2)^2+1


    Step-by-step explanation:


    (f°g)(x) =g(f(x)) =g(3x+2)=(3x+2)^2 +1

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )